2020
DOI: 10.1016/j.heliyon.2020.e03938
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying methods on chemical composition and antioxidant activity of underutilized stinging nettle leaves

Abstract: Stinging nettles provide low-cost quality nutrition for alleviating malnutrition. Previous research on stinging nettles focused mainly on the nutritional quality of fresh leaves. In this study, the effect of drying method on macronutrients, mineral content, ascorbic acid, β-carotene content and total phenols content and antioxidant activity were investigated. The contribution of fresh, oven dried or freeze dried stinging nettle leaves to the required daily value for the nutrients were also determined. Oven dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
47
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 53 publications
11
47
4
Order By: Relevance
“…In our study, the AAC in nettle leaves ranged from 8.17 mg 100 g −1 in April to 0.58 mg 100 g −1 in September ( Table 1 ). These values are lower when compared to the amounts of ascorbic acid reported by other investigators [ 5 , 20 , 21 , 22 ]. This could be influenced by meteorological conditions.…”
Section: Resultscontrasting
confidence: 68%
See 2 more Smart Citations
“…In our study, the AAC in nettle leaves ranged from 8.17 mg 100 g −1 in April to 0.58 mg 100 g −1 in September ( Table 1 ). These values are lower when compared to the amounts of ascorbic acid reported by other investigators [ 5 , 20 , 21 , 22 ]. This could be influenced by meteorological conditions.…”
Section: Resultscontrasting
confidence: 68%
“…According to previous research [ 20 ], ascorbic acid in nettle leaves appears in two forms—ascorbic acid and dehydroascorbic acid. Scientists indicate that the total ascorbic acid content (AAC) may vary from 16.00 to 112.80 mg 100 g −1 of fresh weight (FW) or even to 238 mg 100 g −1 [ 5 , 20 , 21 , 22 ]. In our study, the AAC in nettle leaves ranged from 8.17 mg 100 g −1 in April to 0.58 mg 100 g −1 in September ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids, phenolic acids and other polyphenols as antioxidants can react with the free radicals of macromolecules, preventing undesirable aging processes. The high antioxidant activity of the leaves was confirmed in many of the previously described studies [ 64 , 65 ]. In addition, all the additives used can act as UV radiation absorbers, which was confirmed by UV-Vis spectroscopy analysis.…”
Section: Resultssupporting
confidence: 70%
“…On the basis of the obtained colorimetric results, it can also be observed that UV radiation caused a greater color change than the increased temperature. This is due to the presence of natural stabilizers and antioxidants in common nettle, such as carotenoids and flavonoids, that are less UV resistant [ 38 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%